PENGARUH METODE OUTDOOR STUDY TERHADAP MOTIVASI SISWA KELAS IV SD NEGERI CIBALONGSARI IV - Abdullah, Darda; Rosmala, Melly (STKIP Subang, 2020)
The research aims to increase the motivation of students by Outdoor Study method on the topic of culture diversity, and to find the effect of the used of Outdoor Study method to students motivation. The research is conducted at Cibalongsari IV elementary school in 2019/2020 academic years. The method used in this research is a quasi eksperiment a type of nonequivalent control group design. The subject of this research amounted 56 students, by using sampling technique that is purposive sampling in fourth grade. The instrument collection of data by used questionairs and documentation. The results showed that the Outdoor Study method affected students motivation. It can be seew from the results of coefficient of determination validate the magnitude of student motivation by used conventional method is 0,280, while the magnitude of the effect students motivationsby used Outdoor study method is 0,572. Based on the calculation, is is obtained that the valve of regresions test by the significance grade of 0,05 that is 0,000, then results of the Outdoor Study can increase to learned students motivation of fourth grade.